KARAKTERISTIK PERUBAHAN KEJELASAN BICARA PADA PEMAKAI GIGI TIRUAN LENGKAP DALAM UCAPAN KONSONAN LINGUO PALATAL /C/, /J - Suzan Elias (Faculty of Dentistry, Universitas Indonesia, 2015)
Proper and clear pronounciation are problems that usually rising i patients with edentulous ridge. To overcome that problem a full denture is highly needed, so that the patients can eas as well, to fulfill the esthetic problems and good in speaking. In Phonetics there is a difference between vocal and consonant, it depends on how the modification of the air flow in respiration in the oral cavity. In this research, the point of view is the linguopalatal consonant /c/ an /j/ that had a place of articulation in front of the palatum. In full denture wearers there is a difficulty in pronouncing this consonant properly because the Upper Full Denture has a palatal plate, in which this linguopalatal consonant has a place in the middle of the paalatum. This research evaluated the quality of pronouncing the linguopalatal consonant after the day of insertion, after 3 days, 10 days and also before using denture. 25 respondents using denture for the first time and 3 researchers evaluated the proper and clear pronounciation of 6 words (cacah, cicih, cucu, jajah, jijik, juju). The result of this study is here there is no progress in proper pronounciation using the word cacah, cicih and cucu. On the other hand there is an increase about 20% in good pronouncing the word jajah, and also there is a decreasing percentage in pronouncing word jijik and juju. After day 10, all of the words can be pronounced well except word jijik. So there is a special characteristic in full denture wearers for consonant /c/ and /j/.